SENTENCE OF LIFE IMPRISONMENT IN THE LAW OF BOSNIA AND HERZEGOVINA AND CASE LAW OF THE EUROPEAN COURT OF HUMAN RIGHTS - Miodrag Simović; Marina Simović; Vladimir Simović (Revija za kriminologiju i krivično pravo)
In the system of measures of societal reaction towards the perpetrators of criminal offences, all the modern criminal laws, including the new legislation of Bosnia and Herzegovina, recognise sentences in the first place. They are the main types of criminal sanctions whose purpose can be achieved to the fullest, and that is the protection of society and social goods from all forms and types of injury and threat caused by the commission of criminal offences. Given that in the structure of criminal offences occur those with serious consequences, violating the highest social values, committed with a severe form of guilt by a repeat offender, in concurrence or by a group or organised crime group, it is logical that all penal systems recognise the harshest sentence - longterm or life imprisonment - especially after the abolition of the death sentence - capital punishment, for the severest forms of crimes. The paper analyses issues related to the harshest sentence, long-term, or life imprisonment in Bosnia and Herzegovina, with the special emphasis on the European Court of Human Rights case law.